Is Taiwan’s R&D productivity in decline? A microeconometric analysis - Yang, Chih-Hai; Huang, Chia-Hui (Journal of Business Economics and Management, 2013)
Innovation is widely recognized as the main stimulus of economic growth. Considering that Taiwan has devoted increasingly more efforts to R&D since the late 1980s, a crucial question is posed: did the R&D productivity of firms begin to decline in Taiwan during the post-Asian Financial Crisis period when Taiwan’s economic growth began to decelerate? This study investigates changes in R&D productivity for Taiwan’s manufacturing firms from 1990 to 2003. By employing various approaches to obtain robust results, findings from firm-level microeconometric analysis suggests that overall R&D productivity in Taiwan appears to have been ascendant, particularly during the post-crisis period. This result is also evidenced by segmenting the sample into industry groups, whereby electronics firms have a significantly high R&D productivity growth relative to firms outside the electronics industry. Therefore, the slowdown of Taiwan’s economic growth in the past decade is attributed to other influences rather than a slowdown in R&D productivity.